Grid header election by predetermining in mobile ad-hoc networks. - Tuan, Chiu-Ching (Journal of Applied Science and Engineering)
Mobile ad hoc networks (MANETs) consist of a set of mobile nodes without deploying base stations. Since mobile nodes are energy limited, designing an energy-efficient routing protocol is an important issue in MANETs. Among existing routing protocols, grid routing protocols are usually used for saving energy. In grid routing protocols, only few nodes act as grid headers to maintain connectivity of network and other nodes can be tuned into idle mode to save energy. In traditional grid header election, such as GRID and LB2R, a robust grid header is selected without considering energy consumption. All nodes need to broadcast elected packets to compete as a grid header once the residual energy of current grid header is insufficient. Hence, nodes consume the redundant energy without transmitting data. To solve this problem, we propose a grid header election by predetermining (GHEP) in MANET's. In GHEP, a node will be selected as a candidate node becomes as the new grid header immediately without sending extra controlled packets for election. Simulation results showed that our proposed GHEP outperformed GRID and LB2R in different number and moving speed of nodes. Moreover, GHEP could also save more energy then GRID and LB2R.